Institutional Vulnerability of BUM Desa in Enterprise Management in Central Mamuju Regency - Sabir, Andi Fauzan (Pinisi Business Administration Review, 2026)
BUM Desa were established as policy instruments to strengthen rural economies through the collective management of local resources and village-based enterprises. Despite strong regulatory support and rapid expansion following the Dana Desa policy, many BUM Desa have not been able to manage their enterprises sustainably. This condition indicates the presence of institutional vulnerability that affects organizational performance and continuity. This study aims to analyze institutional vulnerability in the management of BUM Desa enterprises in Central Mamuju Regency. The study employs a qualitative descriptive approach using document-based analysis. The primary data source is the Academic Study on the Development and Empowerment of BUM Desa in Central Mamuju Regency, supported by national policy documents and peer-reviewed academic literature. Data analysis follows the interactive model proposed by Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that institutional vulnerability is most evident in the legal–institutional dimension, as only a small proportion of BUM Desa have obtained badan hukum status, while most remain in registration processes or face administrative barriers. Additional vulnerabilities are reflected in weak organizational structures, limited managerial capacity, and high dependency on village government authority. These vulnerabilities emerge from the interaction between institutional design, governance practices, and policy implementation. Strengthening institutional capacity is therefore essential to support sustainable enterprise management of BUM Desa.